Presentation by Dr. Pascual González Masegosa. Royal Academy of Medicine and Surgery of Valladolid, May 18, 2019. (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
The bullfighting activity, as explained in his speech at this Royal Academy, the Bullfighter and Academic D. Enrique Ponce, is a "Show in which Technique, Art and Risk are combined". No Technique, no Art and... without Risk the show considered as Intangible Cultural Heritage would not make sense.The bullfighting show, despite some historical prohibitions, has remained alive throughout these last five centuries. At present it is going through a certain decline, a bad moment, as shown by the statistics of official bodies, such as the Ministry of Culture. In their analysis corresponding to the year 2016  we can see how the Bullfighting Celebrations in Bullrings have totaled 1958 in all its versions: The Corrida de Toros has accounted for a quarter of all of them (24.2%), followed by the Novilladas without picadores (16.4%), Bullfighting Festivals (13.5%) Novilladas with picadores (12.5%) and Corridas de Rejones (10.8%) With a smaller proportion we cite the becerradas and the festivals or mixed bullfights.